Rancang Bangun Tombol Darurat Bagi Lansia dan Penderita Cardiovascular Berbasis ESP8266 dan Raspberry Pi - Muhammad Yusuf (Journal of Informatics and Communication Technology (JICT), 2020)
An emergency button is a device that can give some warning to targeted devices. The warnings that given by someone are for warn someone that the user is in danger. Emergency button can reduce some mortality and damages caused by cardiovascular. This research are done because there are too much cardiovascular patients and death caused by cardiovascular. This device is for elder who easily in danger like falling. The methods that used are assemble the device, and implement it in daily use.